Challenges Contributing to the General Aviation Weather Problem & Decision Support Systems Technology Recommendations. (September 2018) - King, Jayde; Ortiz, Yolanda; Blickensderfer, Beth; Christy, Emalee
General Aviation (GA) weather related accidents have steadily remained the most fatal accidents and incidents in the GA flight community. The majority of these accidents involve low-experienced Visual Flight Rule (VFR) pilots, inadvertently encountering Instrument Meteorological Conditions (IMC). Previous research indicates, poor inflight weather avoidance could stem from insufficient preflight weather planning. Further investigation reveals, pilots' face many challenges during the preflight planning process, including: poor weather product interpretation/ usability, decision making biases and errors, and inadequate aviation weather experience. However, with new technology on the rise, a preflight decision support tool may help guide novice pilots through the preflight process successfully. This paper will discuss the challenges novice pilots encounter during the preflight process and offer recommendations for applying a preflight decision support tool as a solution.